Serological prevalence of leptospira infection in Malayan Porcupines (Hystrix brachyura) in captivity - Abdul Kadir, Siti Nurdiyana; Bahaman, Abdul Rani; Kumar Sharma, Reuben Sunil; Sugnaseelan, Sumita; Che' Amat, Azlan; Abdul Razak, Mohd Firdaus Ariff (2012)
Leptospirosis is recognised as one of the important zoonotic diseases in the world including Malaysia and rodents are the major natural reservoir of this disease. A study was conducted to determine the serological prevalence of leptospiral infection among a rodent species, the Malayan Porcupine (Hystrix brachyura). A total of 50 serum samples were obtained from the porcupines kept in captivity at the Wildlife Conservation Centre, Sungai Dusun, Selangor. The microscopic agglutination test (MAT) was performed to detect the presence of agglutinating antibodies to a panel of 16 Leptospira serovars (Australis, Autumnalis, Ballum, Bataviae, Canicola, Celledoni, Djasiman, Hardjobovis, Hardjo, Hebdomadis, Hurstbridge, Icterohaemorrhagiae, Javanica, Pomona, Pyrogenes and Sejroe). From the serological test, 18% (9/50) of the porcupines had leptospiral antibodies to serovars Javanica (8%), Hurstbridge (4%), Ballum (2%), Celledoni (2%) and Hardjoprajitno (2%). Hence, this study disclosed that leptospiral infection was prevalent among the Malayan Porcupines and could be a potential source of infection to humans.